Pencemaran Mikroplastik Di Perairan dan Dampaknya terhadap Organisme Perikanan: Sebuah Tinjauan Sistematis - Tiara Zirianda; Abdunnur Abdunnur; Heni Pagoray; Fitriyana Fitriyana; Komsanah Sukarti (Universitas Pahlawan Tuanku Tambusai, 2026)
Microplastic pollution in aquatic environments has emerged as a pressing global environmental concern; however, a comprehensive understanding of its extent and impacts in Indonesia remains limited. This study aimed to analyze the levels and distribution of microplastic contamination across different water body types in Indonesia, identify the characteristics of microplastics found, assess their impacts on fishery organisms, and identify factors influencing contamination and organism vulnerability. A systematic literature review (SLR) following PRISMA 2020 guidelines was conducted, analyzing 17 empirical research articles published between 2021 and 2026 that met pre-defined inclusion criteria. Results revealed that microplastics were detected across all water body types examined—including rivers, reservoirs, lakes, coastal areas, open sea, and mangrove ecosystems—with concentrations ranging from 0.012–0.42 particles/L in water, 320–1,710 particles/kg dry weight in sediment, and 0.5–8.7 particles/individual in organisms. Fiber was the dominant morphological form (94.1% of studies), with polyethylene (PE) and polypropylene (PP) as the most prevalent polymers, and particles <1 mm in size being the most commonly reported. Impacts on fishery organisms included accumulation prevalence approaching 100% in all fish species studied, histopathological damage to gills, liver, and intestines, elevated oxidative stress (increased MDA, altered SOD and CAT activity), and identified trophic transfer in several ecosystems. The primary factors driving contamination were domestic waste (textile fibers), water hydrodynamics, ecosystem type, and organism feeding habits. These findings underscore the urgency of strengthening plastic waste management regulations, standardizing monitoring protocols, and expanding research coverage beyond the island of Java.